1979
DOI: 10.1021/j100475a008
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for hydrogen atom reactions in neopentane-cyclohexane mixtures irradiated at 4.2 K

Abstract: In this paper, a simple model is given to explain why hydrogen atoms produced in crystalline neopentane at 77 K have a high probability of reacting with dilute solute molecules, whereas at 4.2 K they abstract hydrogen from neopentane matrix molecules. The model is based on the following assumptions: at 77 K hydrogen atoms which do not undergo short-range hot abstractions migrate until they encounter a solute molecule, and abstract hydrogen from it. At 4.2 K the hydrogen atoms which would be mobile at 77 K are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…It should be mentioned, however, that Iwasaki, Toriyama and co-workers [44][45][46] ascribed the selective formation of protiated radicals in mixed crystals to reactions of thermal D-atoms rather than to exciton migration. The observed suppression of energy transfer at 4 K was considered to be the main evidence against the exciton mechanism (compare with Section 2.3.1).…”
Section: Events Leading To Radical Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned, however, that Iwasaki, Toriyama and co-workers [44][45][46] ascribed the selective formation of protiated radicals in mixed crystals to reactions of thermal D-atoms rather than to exciton migration. The observed suppression of energy transfer at 4 K was considered to be the main evidence against the exciton mechanism (compare with Section 2.3.1).…”
Section: Events Leading To Radical Formationmentioning
confidence: 99%
“…and R2 H + I~I ~ 1~2 +H2 (2) were considered by Iwasaki and co-workers [44][45][46]48] to be the main mechanism for radical pair production (see Section 2.3.1) and for radical site migration (see Section 2.5), as well as for the preferential formation of protiated radicals in mixed crystals, mentioned above. The fact that no trapped H-atoms were detected in alkanes at 4.2 K [49] was attributed to their rapid tunnel abstraction reaction with surrounding molecules.…”
Section: R~h-~ R~ + Fl (1)mentioning
confidence: 99%
“…A number of methods have been described to include nuclear quadrupole effects smaller than the nuclear Zeeman interaction (8, [11][12][13][14][15][16][17][18][19][20][21]. The general result is to add two or more additional parameters to be determined by the simulated fit to the experimental data which often makes it difficult to obtain a unique set of five or more parameters.…”
Section: Analysis Of Nuclear Modulationmentioning
confidence: 99%
“…in irradiated methanol at 4 K were determined for the first time by Iwasaki and Toriyama in 1978 [22]. Furthermore, they investigated experimentally the reactions occurring by radiolysis of polycrystalline methanol [23] and concluded that the formation of C H 2 0 H is caused by a unimolecular process from CH30., i.e., according to reaction (14).…”
Section: Rimentioning
confidence: 99%